P59 Characteristics of established and newly treated patients with COPD according to GOLD 2017 in a UK primary care population. (December 2018) - Halpin, DMG; de Jong, H; Carter, V; Skinner, D; Price, D
Abstract : Rationale: The 2017 GOLD report proposed a revised assessment scheme for patients with COPD. We have examined the distribution and characteristics of patients with an established diagnosis and those started on maintenance therapy for the first time by GOLD group. Methods: 6940 patients with a recorded diagnosis of COPD on 1/1/2014 in the Optimum Patient Care Research Database (ALL) and 876 patients newly initiated on maintenance therapy (NMT) in 2014 with a two-year follow-up were studied. Both cohorts had data on the number of exacerbations in the previous 12 months, mMRC and FEV1 in the year 2014. Results: Nearly half of patients in both cohorts were GOLD A. There was little difference in the proportion of patients by GOLD stage between the cohorts. In all groups NMT patients were younger. The biggest differences between ALL and NMT were seen in those in GOLD D: NMT patients had higher FEV1, lower mMRC scores and lower exacerbation rates. The commonest therapy started in NMT patients was LAMA followed by ICS/LABA with triple therapy mostly used in GOLD D. Conclusion: Patients started on maintenance therapy were most commonly in GOLD A. Initiation of bronchodilator therapy in most cases was in line with current GOLD recommendations in groups B C and D but there was over initiation of LABA/ICS in groups A and B.